Molecular phylogeny of Neotropical rock frogs reveals a long history of vicariant diversification in the Atlantic forest - Sabbag, Ariadne F. [UNESP]; Lyra, Mariana L. [UNESP]; Zamudio, Kelly R.; Haddad, Celio F. B. [UNESP]; Feio, Renato N.; Leite, Felipe S. F.; Gasparini, Joao Luiz; Brasileiro, Cinthia A. (Elsevier B.V., 2018)
The Brazilian Atlantic coastal forest is one of the most heterogeneous morphoclimatic domains on earth and is thus an excellent region in which to examine the role that habitat heterogeneity plays in shaping diversification of lineages and species. Here we present a molecular phylogeny of the rock frogs of the genus Thoropa Cope, 1865, native to the Atlantic forest and extending to adjacent campo rupestre of Brazil. The goal of this study is to reconstruct the evolutionary history of the genus using multilocus molecular phylogenetic analyses. Our topology reveals 12 highly supported lineages among the four nominal species included in the study. Species T. saxatilis and T. megatympanum are monophyletic. Thoropa taophora is also monophyletic, but nested within T. miliaris. Populations of T. miliaris cluster in five geographically distinct lineages, with low support for relationships among them. Although all 12 lineages are geographically structured, some T. miliaris lineages have syntopic distributions with others, likely reflecting a secondary contact zone between divergent lineages. We discuss a biogeographic scenario that best explains the order of divergence and the distribution of species in Atlantic forest and adjacent areas, and outline the implications of our findings for the taxonomy of Thoropa.
Keywords: Anurans; Cycloramphidae; Genetic diversity; Molecular markers; Thoropa